Digital Education Transforming Higher Education. - Philips, John Arul (2017)
NATIONAL NATIONALMANAGEMENT MANAGEMENT ACCOUNTING ACCOUNTINGCONFERENCE CONFERENCE Session pm Cyber Security, Risk Management, Governance and Compliance Introduction by Chairman Cyber Security Cyber Threat Management Mr. Vishal M Jain Partner Deloitte India Risk Management in the Digital Economy Mr. Uantchern Loh CEO, Asia Pacific Black Sun Plc, Singapore Governance, Risk and compliance in a digital world. Mr. Sujit Christy Director Layers7 SeguroConsultoria Private Limited National Cyber Security Mr. John Tan Wee Keong Project Manager S T Electronics (Info Security Pvt Ltd) Singapore Q&A Lunch Session pm Digital Education and Skills Development Introduction by Chairman Digital Education Transforming Higher Education to be a Knowledge Economy Prof. Dr. John Arul Phillips Dean Asia e University Transitioning to Digital Potentials and Practices in Sri Lankan Higher Education Prof. Shironica P. Karunanayaka Professor in Educational Technology The Open University of Sri Lanka Digital Skill Development and Workforce Transformation Prof Ajantha Dharmasiri President Institute of Personnel Management (IPM) and Director PIM Q&A Session pm Panel Discussion Digital Transformation Building the Next Generation Accountants Chairman / Moderator Mr. Dinesh Weerakkody Advisor Ministry of National Policies and Economic Affairs Panelists Prof. Samanthi Senaratne Professor Dept. of Accounting University of Sri Jayewardenepura Mr. Adrian Perera ACCA UK (Sri Lanka Branch) Prof. Lakshman R. Watawala President CMA Sri Lanka Mr. Lasantha Wickremasinghe President CA Sri Lanka Mr. Anuj Jain Senior Vice President (Finance) Lanka IOC PLC Mr. Ronnie Peiris Group Finance Director John Keells Holdings PLC Mr. Asite D.B. Talwatte Chairman Management Systems (Pvt) Limited Mr. Uantchern Loh CEO Black Sun Plc, Singapore Strategy & Integrated Thinking South Africa Mr. Graham Terry, Consultant Mr. Vishal M Jain, Partner Deloitte India Dato.AhmadFarisYahaya, Former Managing Director CyberviewSdnBhd Malaysia Closing Remarks Tea Meant For: CMA Members, CEOs, Directors, CFOs, Senior Managers, Management Accountants, Financial Accountants, Financial Analysts, Professionals, Academics and Government Officials. Investment : Members Rs. 17,500/NON Members Rs. 19,500/ The Institute of Certified Management Accountants of Sri Lanka No. 29/24, Visakha Private Rd,